Állambiztonság és rendszerváltás 1981–1989 - Bertalan, Péter (Acta Scientiarum Socialium, 2014)
State Security and Change of Regime 1981–1989 In contradiction to the long 19th century, the historical public opinion calls the 20th century the short century. The meaning of the attribute is in connection with the densification of events. The tragic, from day to day changing events of the two world wars and the political happenings reported by the modern media every minute, hour and day, make the sense of relative shortening of time. We cannot properly estimate and evaluate the weight and significance of events and happenings due to the abundance of information. A consequence of this is some distortion in our political and historical views, the deficiency of judgement of political events, and dull sense of reality. It happens that the media and the political sources remains silent about the events. The lack of information causes ignorance and misinterpretation, making the clear view of politics difficult. Till the time of the unification of the two Germanies, the historical lines of force are easily visible, along which the events take place. After 1989-90 comes uncertainty. There are so deep currents of history, the effects of which are difficult to calculate. The events to come are difficult to predict. The political events seem to become chaotic. The idea of the well-known philosophy of Madách comes to mind: „age, a stream, which leads or submergesâ€¦” The concept of submersion is the literary allegory of the frequently appearing sense of historical fatalism.
Keywords: historical public; philosophy; Madách; age; historical fatalism